Ethnomathematics: Urgency and Challenges of Implementation in Elementary School Mathematics Learning - Amelia Dwi Astuti; Achmad Zainul Rozikin (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Background: Ethnomathematics is a mathematics learning approach integrating students' cultural and social contexts into mathematical content. This approach is important for enhancing the relevance and understanding of mathematics at the elementary school level, particularly in fostering multicultural awareness and promoting social justice. However, its implementation still faces various challenges, including issues related to the curriculum, teacher preparedness, and the availability of culture-based teaching materials. Aim: This study aims to analyze the urgency of implementing ethnomathematics in elementary mathematics education and to identify the challenges encountered in its application. A literature review method was employed, analyzing journal articles, books, and previous research on ethnomathematics, elementary mathematics curricula, and culture-based learning practices. Data were collected from databases such as ERIC, Google Scholar, and Scopus and then analyzed thematically. Result and Discussions: The findings indicate that ethnomathematics is highly urgent for (1) increasing students' learning motivation through familiar cultural contexts, (2) developing critical thinking regarding socio-cultural realities, and (3) supporting inclusive education. However, implementation challenges include (1) a lack of teacher training in designing culture-based materials, (2) limited standardized ethnomathematics resources, and (3) resistance from an education system still oriented toward national examinations.